FRI0096 Influence of dose titration of concomitant steroid and methotrexate during biologic therapy on remission rates in patients with rheumatoid arthritis according to the new ACR/EULAR remission criteria in daily practice based on the iorra cohort. (23rd January 2014) - Shimizu, Y.; Tanaka, E.; Inoue, E.; Shidara, K.; Hoshi, D.; Sugimoto, N.; Sato, E.; Seto, Y.; Momohara, S.; Nakajima, A.; Taniguchi, A.; Yamanaka, H.
Abstract : Background: After the introduction of biologics for the treatment of patients with active rheumatoid arthritis (RA), clinical remission has become an achievable and realistic therapeutic goal. In clinical trials, remission rates in patients receiving biologics are assessed under a fixed-dose regimen of steroid and/or methotrexate. However, in daily practice, the dose of concomitant steroid and/or methotrexate is often titrated according to the patient's response to therapy; thus, remission rates might be influenced by this titration. Objectives: To examine the relationship between remission rate and concomitant use of steroid and methotrexate in RA patients after starting biologics therapy in daily practice. Methods: We have established a large observational cohort of RA patients, IORRA (Institute Of Rheumatology, Rheumatoid Arthritis), in our institute since October 2000. Essentially all RA patients who attend our clinic are asked to complete questionnaires every 6 months. Clinical information, including physician's evaluations and laboratory data, is collected biannually (April and October). As a result, more than 5000 RA patients were registered. All RA patients who commenced treatment with biologics from 2008 to 2010 were extracted from the IORRA database. The 28-joint Disease Activity Score (DAS28), remission rate based on the ACR/EULAR remission criteria, and frequencies of use and doses of methotrexate and steroid before treatment and 2 years after initiation of each biologic drug were calculated. Results: Average DAS28 before/after the initiation of infliximab (INF: n=98), etanercept (ETA: n=181), tocilizumab (TOC: n=90) and adalimumab (ADA: n=101) were 4.54/2.96, 4.35/2.93, 4.63/2.73 and 4.23/3.30, respectively. The remission rates according to Boolean (trial) criteria/Simplified Disease Activity Index (SDAI)/Boolean (practice) criteria/Clinical Disease Activity Index (CDAI) in patients treated with INF, ETA, TOC and ADA were 14.3%/33.7%/17.4%/29.6%, 26.0%/33.2%/27.1%/31.5%, 15.6%/24.4%/15.6%/22.2% and 20.8%/33.7%/23.8%/30.7%, respectively. The frequencies of use and average dose of steroid in patients treated with biologics (n=470) before treatment and 2 years after initiation of biologics were 58.9% (4.96 mg/day) and 51.5% (4.84 mg/day), respectively. Although both the frequencies of use and doses of steroid decreased during treatment with biologics (with the exception of steroid dose for patients treated with ADA), approximately 50% of patients continued receiving steroids 2 years after starting the biologic agent. The frequencies of use of methotrexate decreased in patients receiving ETA and TOC but increased in patients treated with ADA; doses of methotrexate decreased in patients receiving INF and ETA but increased in patients treated with TOC and ADA. Conclusions: Since the concomitant dose of methotrexate and steroid was titrated commonly in RA patients receiving biologics in daily practice, care should be exercised when interpreting remission rates of patients treated with biologics in daily practice. Disclosure of Interest: Y. Shimizu: None Declared, E. Tanaka: None Declared, E. Inoue: None Declared, K. Shidara: None Declared, D. Hoshi: None Declared, N. Sugimoto: None Declared, E. Sato: None Declared, Y. Seto: None Declared, S. Momohara: None Declared, A. Nakajima: None Declared, A. Taniguchi: None Declared, H. Yamanaka Grant/Research support from: IORRA study is supported by 40 pharmaceutical companies;Asahikasei Kuraray Medical Co., Ltd. Abbott Japan Co., Ltd. Asahikasei Pharma Corporation Astellas harma Inc. AstraZeneca K.K. Bristol-Myers Squibb Chugai Pharmaceutical Co., Ltd. Daiichi Fine Chemical Co., Ltd. Daiichi Sankyo Co., Ltd. Dainippon Sumitomo Pharma Co., Ltd. Eisai Co., Ltd. GlaxoSmithKline K.K. Hisamitsu Pharmaceutical Co., Inc. Janssen Pharmaceutical K.K. Japan Tobacco Inc. Kaken Pharmaceutical Co., Ltd. Kissei Pharmaceutical Co., Ltd. Kowa Pharmaceutical Co.Ltd. Maruho Co., Ltd. Mitsubishi Chemical Medience Corporation Mitsubishi Tanabe Pharma Corporation Mochida Pharmaceutical Co., Ltd. MSD K.K., Mundipharma K.K. Nippon Chemiphar Co., Ltd. Nippon Shinyaku Co., Ltd. Novartis Pharma K.K. Otsuka Pharmaceutical Co., Ltd. Pfizer Japan Inc. Sanofi-Aventis K.K. Santen Pharmaceutical Co., Ltd. Sanwa Kagaku Kenkyusho Co., Ltd. Sekisui Medical Co., Ltd. Shionogi Co., Ltd. Taishotoyama Pharmaceutical Co., Ltd. Takeda Pharmaceutical Company Limited Teijin Pharma Limited Torii Pharmaceutical Co., Ltd. UCB Japan Co. Ltd. ZERIA Pharmaceutical Co., Ltd.Consultancies, speaking fee from Abbott, AstraZeneca, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi Tanabe., Pfizer, Takeda, Teijin Pharma, UCB.